The balance of crew rowing boats / Volker Nolte and Siobhan McLaughlin - Nolte, Volker; McLaughlin, Siobhan (Faculty of Sports Science and Recreation, 2005)
The purpose of this study was to examine the feasibility of a method to measure the rolling of rowing shells during normal performance, and the comparison of balance patterns for several crews of different experience levels. One novice eight, a club four and two National team eights were analyzed during regular training routines. The balance measurement tool, a Silva Level, did not interfere with crew performance and the video analysis allowed accurate measurements to 0.5 deg at a sampling rate of 30 Hz. Although the study was designed as a pilot project, the results showed clear tendencies. Balance improved with the experience level of the crews. Boats seemed to be more balanced at higher stroke rates. Surprisingly, all crews appear to learn more to the same side, which could be connected with the rigging of the boats. Also, balance can be improved through appropriate training.